Cyber Security Analysis in Cyber Defense for DrNGPASC in Coimbatore City - Dr. N. Vanitha (International Journal of Engineering and Management Research, 2023)
Cybersecurity is a progressively vital concern in today's advanced age. With the expanding utilize of innovation in different segments, cyber assaults have gotten to be more modern and broad, posturing a critical danger to people, organizations, and governments. Cyber defense is vital in securing against these assaults, and cyber security examination plays a key part in creating compelling defense techniques. This paper presents a comprehensive investigation of cyber security within the setting of cyber defense. It analyses the different sorts of cyber assaults and the procedures utilized by cyber criminals to breach security frameworks. It moreover audits the current state of cyber defense methodologies and innovations, highlighting their qualities and shortcomings. The paper proposes a system for cyber security examination in cyber defense, which incorporates distinguishing potential dangers, surveying their affect, and creating fitting defense methodologies. The system consolidates an extend of strategies, counting hazard appraisal, defencelessness investigation, and occurrence reaction arranging in Dr.N.G.P. Arts and Science College, Coimbatore. The discoveries of this work paper recommend that cyber security investigation may be a critical component of cyber defense, which a proactive approach is required to successfully relieve the dangers postured by cyber assaults. The system proposed in this paper gives a valuable device or organizations and governments to create viable cyber defense methodologies and secure against cyber dangers.